Vilnius Declaration on chronic respiratory diseases: multisectoral care pathways embedding guided self‐management, mHealth and air pollution in chronic respiratory diseases. Issue 1 (28th January 2019) - Valiulis, A.; Bousquet, J.; Veryga, A.; Suprun, U.; Sergeenko, D.; Cebotari, S.; Borelli, D.; Pietikainen, S.; Banys, J.; Agache, I.; Billo, N. E.; Bush, A.; et al.
Abstract: Background: Over 1 billion people suffer from chronic respiratory diseases such as asthma, COPD, rhinitis and rhinosinusitis. They cause an enormous burden and are considered as major non‐communicable diseases. Many patients are still uncontrolled and the cost of inaction is unacceptable. A meeting was held in Vilnius, Lithuania (March 23, 2018) under the patronage of the Ministry of Health and several scientific societies to propose multisectoral care pathways embedding guided self‐management, mHealth and air pollution in selected chronic respiratory diseases (rhinitis, chronic rhinosinusitis, asthma and COPD). The meeting resulted in the Vilnius Declaration that was developed by the participants of the EU Summit on chronic respiratory diseases under the leadership of Euforea. Conclusion: The Vilnius Declaration represents an important step for the fight against air pollution in chronic respiratory diseases globally and has a clear strategic relevance with regard to the EU Health Strategy as it will bring added value to the existing public health knowledge.